Pengembangan Media Pembelajaran Mobile Learning Berbasis Blended Learning pada Teks Cerita Rakyat Sumatera Utara - Roberto Kaban; Tri Indah Prasasti (JUKI : Jurnal Komputer dan Informatika, 2022)
Abstract. This learning media is packaged in the form of an android application that will be used by students, they will also get the value of local wisdom from the North Sumatran folklore learned. This research uses a qualitative descriptive approach with quantitative data collection. The results of the research, the first is the media development process using the 4D Thiagarajan method, namely define, design, develop, and disseminate. Second, validation results by material experts with an average percentage of 96%, validation of media experts with an average assessment percentage of 87%, individual trials with an average percentage of 87%, small group trials with an average percentage of 88%, and limited field trials with an average percentage of 90%. Learning outcomes on folklore text material after using blended learning-based learning media with an average score of 82.81 and an average score before using blended learning-based learning media of 67.65. Keyword : blended learning, mobile learning, learning media, Android Application.